EVALUASI PROGRAM LEMBAGA KETERAMPILAN KEAGAMAAN (LKK) DI UIN ANTASARI BANJARMASIN - Muhammad Helmi (ADDABANA: Jurnal Pendidikan Agama Islam, 2021)
Abstract: Religious skills institution program which is a forum for developing students' knowledge and skills to equip them to carry out community service (KKN). The educational backgrounds are different and there are some students who are not yet fluent in reading the Koran. This research aims to evaluate the context, input, process and product using the CIPP model in the religious skills institute program at UIN Antasari. This type of research is field research with a qualitative descriptive approach. Data analysis uses the Miles and Huberman analysis model. Techniques for checking data validity include increasing persistence and triangulation (sources and techniques). The research results found that the context of this program in each faculty had been implemented in accordance with the expectations and objectives that had been set. Evaluation of input in each faculty shows that the availability of teachers, students, curriculum, procedures and rules as a whole is appropriate and has been fulfilled. However, the facilities and infrastructure as well as financing can still be improved. Evaluation of the process at each faculty shows that the program process at the religious skills institution is running smoothly to provide students with knowledge and preparation for leading religious activities in the community. However, it is necessary to equalize all activities, processes and implementation times for each faculty. Product evaluation at each faculty is different in terms of the graduation assessment aspect, but there are programs that are only carried out in 1 day, which is felt to be less than optimal in delivering material and practice. It is recommended that this LKK program continue to be implemented even during the Covid 19 pandemic, allocate funds according to needs, synchronize the process and activity curriculum for all faculties and the implementation time can be increased.Keywords: CIPP, LKK, Program Evaluation.Abstrak: Program lembaga keterampilan keagamaan yang menjadi wadah pengembangan pengetahuan dan keterampilan mahasiswa/i untuk membekali mereka dalam melakukan pengabdian masyarakat (KKN). Latar pendidikan yang berbeda serta terdapat beberapa mahasiswa/i yang belum lancar dalam membaca Alquran. Penelitian ini bertujuan untuk mengevaluasi konteks, input, proses, dan produk dengan menggunakan model CIPP pada program lembaga keterampilan keagamaan di UIN Antasari. Jenis penelitian ini ialah penelitian lapangan dengan pendekatan deskriptif kualitatif. Analisis data menggunakan model analisis Miles dan Huberman. Teknik pengecekan keabsahan data di antaranya meningkatakan ketekunan dan triangulasi (sumber dan teknik). Hasil penelitian ditemukan bahwa konteks program ini di setiap fakultas telah dilaksanakan sesuai dengan harapan dan tujuan yang telah ditetapkan. Evaluasi input di setiap fakultas menunjukkan bahwa ketersedian pengajar, mahasiswa/i, kurikulum, prosedur dan tata tertib secara keseluruhan sesuai dan sudah terpenuhi. Namun bagian sarana dan prasarana serta pembiayaan masih bisa ditingkatkan. Evaluasi proses di setiap fakultas menunjukkan bahwa proses program pada lembaga keterampilan keagamaan berlangsung dengan lancar untuk memberikan ilmu dan persiapan bekal mahasiswa/i dalam memimpin kegiatan keagamaan di masyarakat. Namun perlu disamakan untuk setiap fakultas dari seluruh kegiatan, prosesnya, serta waktu pelaksanaannya. Evaluasi produk pada setiap fakultas berbeda-beda pada aspek penilaian kelulusannya, namun terdapat program yang hanya dilakukan dalam waktu 1 hari, dirasa kurang maksimal dalam penyampaian materi serta praktek. Program LKK ini direkomendasikan agar terus dilaksanakan walau pada masa pandemi Covid 19, alokasi dana yang sesuai kebutuhan, proses dan kurikulum kegiatan yang disinkronkan untuk semua fakultas serta waktu pelaksanaan yang bisa ditambah.Kata Kunci: CIPP, Evaluasi Program, LKK.